For autistic persons by autistic persons: Acceptability of a structured peer support service according to key stakeholders - Alena Valderrama; Alejandra Martinez; Kathleen Charlebois; Lucila Guerrero; Baudouin Forgeot d'Arc (Wiley, 2023)
Abstract Introduction Social support is a protective factor in the mental health of autistic people. Furthermore, prejudice regarding autistic people is a constraint for the development of social support programmes by autistic peers. Methods The objective of this study is to describe the anticipated acceptability of structured peer support programmes for and by autistic persons. Fifteen key stakeholders (six autistic adults, four caregivers and five service providers) participated in in‐depth semistructured interviews. A qualitative thematic analysis of the content of the verbatim was carried out. Findings We found that while a structured peer social support programme is acceptable to autistic people and caregivers, there was no consensus among service providers. The latter expressed doubts about the ability of autistic people to offer support. The framing of discussions between peers, the training of peer helpers, the support for autistic leadership and an organization that considers the communicational and sensory characteristics of autistic persons, could influence adherence to such a programme. Moreover, a space without service providers is an important condition for the acceptability of a peer support programme. Conclusion A structured peer support service for and by autistic persons could be an innovative way to answer the unmet support needs of autistic people. It seems essential to anticipate potential barriers and facilitators and to communicate among health professionals to promote this approach and reduce possible prejudice about the ability of autistic people to offer support to their peers. More studies are necessary. Patient or Public Contribution Fifteen key stakeholders who are involved in autistic people's trajectory of service and support participated in this research. We are a research team composed of healthcare professionals and researchers, in addition to one member of our team being an autistic advocate and a mental health peer‐support mentor. Two members of our team are also parents of autistic children. The comprehensibility of the questions for the interview was consulted and discussed with one autistic advocate‐collaborator.